A Comparative Analysis of Rhetorical Move and Genre Knowledge Development of English and Indonesian Thesis - Ummu Hani Assyita; Oikurema Purwati; Syafi'ul Anam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
A number of studies have shown that genre analysis through move analysis is a practical approach to identifying complexity in writing research papers (RAs). However, the development of general knowledge embodied in abstract discourse patterns is rarely known. This study aims to clarify whether educational level influences the development of general knowledge, especially in the field of abstract research. Using Hyland's (2000) five-step analysis model, this study analyzes the comparison and identity of thesis abstracts in English and Indonesian. The results of the analysis showed several differences and similarities in the realization of abstract discourse patterns in the final project abstracts in English and Indonesian. As for genre knowledge, its development is expressed in the level of learning, from undergraduate to postgraduate. As can be seen from the thesis abstracts in both languages, Move1 (Introduction) presents a richer variety of step-by-step implementations. The analysis also shows that there are no significant differences in the development of genre knowledge across languages and study areas. It is suggested to have more subject data for further comparative research on this particular topic. Keywords: Abstract, Abstract discourse pattern, thesis, English genre knowledge, Indonesian.